Efficient Generation and Transcriptomic Profiling of Human iPSC-Derived Pulmonary Neuroendocrine Cells - Pooja Hor; Vasu Punj; Ben A. Calvert; Alessandra Castaldi; Alyssa J. Miller; Gianni Carraro; Barry R. Stripp; Steven L. Brody; Jason R. Spence; Justin K. Ichida; Amy L. Ryan (Firth); Zea Borok (iScience, 2020)
Summary: Expansion of pulmonary neuroendocrine cells (PNECs) is a pathological feature of many human lung diseases. Human PNECs are inherently difficult to study due to their rarity (<1% of total lung cells) and a lack of established protocols for their isolation. We used induced pluripotent stem cells (iPSCs) to generate induced PNECs (iPNECs), which express core PNEC markers, including ROBO receptors, and secrete major neuropeptides, recapitulating known functions of primary PNECs. Furthermore, we demonstrate that differentiation efficiency is increased in the presence of an air-liquid interface and inhibition of Notch signaling. Single-cell RNA sequencing (scRNA-seq) revealed a PNEC-associated gene expression profile that is concordant between iPNECs and human fetal PNECs. In addition, pseudotime analysis of scRNA-seq results suggests a basal cell origin of human iPNECs. In conclusion, our model has the potential to provide an unlimited source of human iPNECs to explore PNEC pathophysiology associated with several lung diseases.